Hidden Object Game As A Supporting Media For The Introduction Of New Vocanulary - Setiasih Niode, Syarifah F; Grahita, Banung; Sulistyaningtyas, Tri (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
Teaching and learning new/foreign vocabulary (language) using game must consider the needs and objectives of teaching and learning. Hidden object games are a type of puzzle game that has many educational benefits. The purpose of this study is to analyze hidden object games by formulating how hidden object games can be a stimulate medium for learning vocabulary, formulating elements of vocabulary education in them, and describing the motivation to recognize and increase insight into new/foreign language vocabulary for hidden object game players. The method for analyzing hidden object games as educational media uses the basic element game theory approach by Fullerton which focuses on analysis on the formal and dramatic elements of games for learning purposes. The results of the study show that hidden object games can educate and increase the players' vocabulary knowledge independently, especially the initial level vocabulary, namely receptive types, basic noun word classes. Hidden object games can accommodate vocabulary learning at the pre-teaching stage for beginner levels. However, hidden object games have not been able to maximize their benefits for higher vocabulary educational purposes such as productive vocabulary.Keywords: Hidden object game; Educational Game; Vocabulary Learning